Falling Through Time: The Height of Military Conscripts in the Viceroyalty and the Republic of New Granada, 1720-1840 - Meisel Roca, Adolfo; Nieto Martelo, Brandon (Tiempo y economía, 2026)
There are no estimates of the height of Colombians during the 18th and early 19th centuries. This article contributes to closing this gap. We have constructed a database using military affiliations found in the Archivo General de la Nación, comprising a total of 373 observations (male recruits). The results show a sustained decrease in height during the 18th and first decades of the 19th century. In the case of conscripts born in New Granada, the average height declined from 167.8 cm in 1720 to 164.6 cm in 1800. We argue that these results are mainly explained by the deterioration in the biological standard of living due to numerous epidemics—especially of smallpox—the presence of extreme climatic conditions such as droughts, floods, and frosts, and the rapid increase of the population, which was still recovering from the demographic catastrophe of the 16th century.